2013
DOI: 10.1016/j.jmmm.2013.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Possibility of spin-polarized electric current through Mn-, Fe-, Co-, or Ni-doped BaSi2 predicted by their calculated densities of states

Abstract: Electronic energies and spin-resolved electronic densities-of-states (DOSs) of BaSi2 whose vacant space is occupied by magnetic elements (Mn, Fe, Co and Ni) are calculated using a first-principle pseudopotential method based on the density-functional theory (DFT) with the generalized gradient approximations. Interstitial compounds of these magnetic elements and BaSi2 will be energetically possible and interstitial occupancy of BaSi2 by Fe and, especially, Co atoms will make the materials half-metallic in case … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…We also had to ensure consistency with our previous studies on Mg 2 Si and other semiconducting alkaline-earth and alkali metal silicides. [4][5][6][7][8][9][10][11][12][21][22][23][24][25][26][27][28][29][30][31] The kinetic cutoff energy for the plane wave expansion of the wavefunctions was set at 380 eV, corresponding to a fast Fourier transformation grid of 36 × 36 × 36. The Monkhorst-Pack (M-P) scheme 32) was used for k-point sampling for the total energy calculations with spacing of 0.4 nm −1 in the reciprocal space, which corresponded to mesh parameters of 4 × 4 × 4 and produced 32 points sampled from the irreducible part of the Brillouin zone.…”
Section: Structures Consideredmentioning
confidence: 99%
“…We also had to ensure consistency with our previous studies on Mg 2 Si and other semiconducting alkaline-earth and alkali metal silicides. [4][5][6][7][8][9][10][11][12][21][22][23][24][25][26][27][28][29][30][31] The kinetic cutoff energy for the plane wave expansion of the wavefunctions was set at 380 eV, corresponding to a fast Fourier transformation grid of 36 × 36 × 36. The Monkhorst-Pack (M-P) scheme 32) was used for k-point sampling for the total energy calculations with spacing of 0.4 nm −1 in the reciprocal space, which corresponded to mesh parameters of 4 × 4 × 4 and produced 32 points sampled from the irreducible part of the Brillouin zone.…”
Section: Structures Consideredmentioning
confidence: 99%
“…Since the calculation method and calculated structures used in this work are similar to those applied in the previous study, 15) they are only briefly described here.…”
Section: Calculated Structuresmentioning
confidence: 99%
“…For example, the n-type conduction of Ga-or Cu-doped BaSi 2 can be understood by assuming that the doped atoms occupy some interstitial sites of the BaSi 2 lattice. 13,14) In our previous paper, 15) we observed that BaSi 2 , with its interstitial sites occupied by Fe-or Co-atoms, may function as a half-metal, although analysis of the stability of these compounds has been left for future study. In the present work, we have performed energetic calculations on the possible occupancy of the interstitial sites of BaSi 2 using light elements, i.e., 2p-, 3s-, and 3d-elements, for further understanding of the possible interstitial doping.…”
Section: Introductionmentioning
confidence: 98%